A Case of the TOF with APV Complicated with Polyhydramnios and Severe Bronchomalacia - Ali Seven; Emine Esin Yalinbas; Rahmi Ozdemir (Hindawi Limited, 2016)
Absent pulmonary valve syndrome (APVS) is a rare congenital heart disease with severe pulmonary insufficiency, characterized with aneurysmal dilation in the pulmonary artery and one or both of its branches. We presented a rare case with APVS and literature review in this letter. Prenatal USG examination of the fetus at the 26th week of gestation revealed severe polyhydramnios, dilatation at right ventricle, and abnormal appearance of the heart. At the 31st gestational week, the baby was born with cesarean section. The newborn had right heart failure but had no hydrops fetalis. Therefore, severe respiratory distress observed in the infant has been associated with pulmonary complications. The infant, who had respiratory acidosis according to blood gas analysis, was intubated and attached to mechanical ventilator. Despite progressively increased respiratory support and other interventions, the infant died on the 3rd day of admission. Compression against bronchial tree and esophagus due to dilated pulmonary artery and its branches may inevitably lead to bronchomalacia and polyhydramnios. In conclusion, presence of polyhydramnios and the possibility of severe bronchomalacia should be kept in mind; and due to the risk of early neonatal mortality, delivery should be performed in a center where pediatric heart surgery is available.